A coated sodium ion layered oxide positive electrode material and preparation method thereof

The sodium tungstate coating material produced by the reaction of tungstate and sodium salts is subjected to liquid phase coating on the sodium ion layered oxide positive electrode material, which solves the problem of poor conductivity of the existing coating layer and improves the transfer rate of sodium ions and Battery rate performance and cycle stability.

CN116534917BActive Publication Date: 2025-02-18NANTONG RESHINE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310649986.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-02-18
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The existing sodium ion layered positive electrode material has poor electrical conductivity, which limits the transmission of sodium ions, and thus affects the rate performance and cycle stability of the battery.

Method used

The sodium tungstate coating material is directly reacted with tungstate and sodium salt to form a slurry-like sodium tungstate coating material, and the sodium ion layered oxide positive electrode material substrate is coated through liquid phase coating technology to form a coated sodium ion layer. Oxide positive electrode material.

Benefits of technology

It improves the transfer rate of sodium ions, reduces the impedance of sodium ions diffusion, improves the rate performance and cycle stability of the material, and enhances the uniformity and protection effect of the coating layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116534917B_ABST
    Figure CN116534917B_ABST
Patent Text Reader

Abstract

The present invention provides a coated sodium ion layered oxide positive electrode material and a preparation method thereof, which relates to the field of battery materials. The preparation method comprises: preparing a powdered sodium ion layered oxide positive electrode material substrate using a layered oxide precursor and a sodium salt; mixing and reacting tungstic acid and a sodium salt to obtain a slurry-like sodium tungstate coating material; respectively adding the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate to an organic solvent according to a preset ratio, stirring and mixing, then filtering and drying, and performing heat treatment to obtain a coated sodium ion layered oxide positive electrode material. The present invention provides a fast transmission channel for sodium ion diffusion, and the coating layer can effectively reduce the side reactions on the surface of the positive electrode material, thereby facilitating the improvement of the rate performance and cycle stability of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a coated sodium ion layered oxide positive electrode material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries have attracted much attention in recent years due to their abundant sodium resources, wide distribution, and low cost. Compared with other types of cathode materials, layered cathode materials have become the mainstream research and development direction due to their advantages such as high energy density, excellent cycle performance, and good rate performance.

[0003] At present, the widely used means to modify sodium ion layered positive electrode materials include surface coating, such as coating with oxides and fluorides, etc., which can improve the electrochemical properties of the positive electrode materials by inhibiting phase changes and changes in material structure during the reaction process. When applied to sodium ion batteries, it can also play a role in isolating external moisture and electrolyte corrosion. However, these coating layers have poor electrical and sodium conductivity, which is not conducive to the transmission of sodium ions and is not conducive to improving the battery's rate performance and cycle stability.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a coated sodium ion layered oxide positive electrode material and a preparation method thereof, which can improve the transmission of sodium ions and simultaneously improve the rate performance and cycle stability of the battery.

[0006] To achieve the above object, a technical solution adopted by the present invention is: to provide a method for preparing a coated sodium ion layered oxide positive electrode material, comprising:

[0007] A powdered sodium ion layered oxide positive electrode material substrate is prepared by using a layered oxide precursor and a sodium salt;

[0008] Mixing tungstic acid and sodium salt and reacting them to obtain a slurry-like sodium tungstate coating material;

[0009] The sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate are respectively added to an organic solvent according to a preset ratio, stirred and mixed, filtered and dried, and heat treated to obtain a coated sodium ion layered oxide positive electrode material.

[0010] Furthermore, when the tungstic acid and the sodium salt are mixed, the molar ratio of tungsten to sodium is 1:2.

[0011] Furthermore, the sodium salt is sodium carbonate and / or sodium hydroxide.

[0012] Furthermore, the preset ratio is a molar ratio of 0.1 to 5:100.

[0013] Furthermore, the organic solvent is ethanol, isopropanol or ethylene glycol.

[0014] Furthermore, the stirring and mixing time is 15 to 120 minutes; the heat treatment conditions are: temperature at 400 to 750° C., and time at 8 to 15 hours.

[0015] Furthermore, the step of preparing a powdered sodium ion layered oxide positive electrode material substrate using a layered oxide precursor and a sodium salt comprises:

[0016] The layered oxide precursor and the sodium salt are mixed uniformly, wherein the chemical formula of the layered oxide precursor is Ni a Mn b M c (OH)2 or Ni a Mn b M c CO3, where 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.4, a+b+c=1, M is Fe 2+ , Cu 2+ and Zn 2+ One or more of;

[0017] The mixed materials are sintered and crushed to obtain the sodium ion layered oxide positive electrode material substrate having a chemical formula of Na x Ni a Mn b M c O2, where 0.9≤x≤1.0.

[0018] Furthermore, the sintering conditions are: temperature between 850 and 980° C. and time between 8 and 15 hours.

[0019] To achieve the above object, another technical solution adopted by the present invention is: to provide a coated sodium ion layered oxide positive electrode material prepared according to the preparation method described in the above technical solution.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention uses tungstic acid and sodium salt to directly react to generate a slurry-like sodium tungstate coating material, and then performs liquid phase coating on the positive electrode material substrate, and utilizes the good conductivity of sodium tungstate to provide a fast transmission channel for sodium ion diffusion, which is beneficial to improve the ion transmission rate in the positive electrode material during charging and discharging, reduce the impedance of sodium ion diffusion, and improve the rate performance of the material. At the same time, the coating layer protects the surface of the positive electrode material, improves the stability of the interface, can effectively reduce the side reactions on the surface of the positive electrode material, and is beneficial to improve the cycle stability of the positive electrode material. Secondly, the coating layer formed by liquid phase coating in the present invention has a controllable thickness, and the particles are not easy to agglomerate, which can effectively improve the uniformity of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present application, but do not constitute an improper limitation of the present invention. In the drawings:

[0023] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a coated sodium ion layered oxide positive electrode material according to the present invention;

[0024] Figure 2 This is the XRD pattern of the positive electrode material of Example 1;

[0025] Figure 3 It is a comparison chart of the rate performance of comparative example / embodiment 1 / embodiment 2 / embodiment 3;

[0026] Figure 4 It is a comparison chart of the cycle performance of comparative example / embodiment 1 / embodiment 2 / embodiment 3. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0028] Among the existing sodium ion layered cathode materials, surface coating is widely used, such as coating with oxides and fluorides, etc., which can improve the electrochemical properties of the cathode materials by inhibiting phase changes and changes in material structure during the reaction process. When applied to sodium ion batteries, it can also isolate them from external moisture and electrolyte corrosion. However, these coating layers have poor electrical and sodium conductivity, which is not conducive to the transmission of sodium ions and is not conducive to improving the battery's rate performance and cycle stability.

[0029] In view of this, the present invention proposes a method for preparing a coated sodium ion layered oxide positive electrode material, which improves the ion transfer rate during the charging and discharging process of the material, reduces the impedance of sodium ion diffusion, and improves the rate performance of the material. At the same time, the coating layer protects the surface of the material, improves the stability of the interface, and is beneficial to the improvement of the cycle stability of the material.

[0030] According to the first aspect of the present invention, a method for preparing a coated sodium ion layered oxide positive electrode material is described in detail in Figure 1 The preparation method includes the following steps S11 to S13.

[0031] Step S11, preparing a powdery sodium ion layered oxide positive electrode material substrate using a layered oxide precursor and a sodium salt.

[0032] Specifically, the layered oxide precursor and the sodium salt can be mixed evenly, and then sintered and crushed. The layered oxide precursor hydroxide or carbonate system has a chemical formula of Ni a Mn b M c (OH)2 or Ni a Mn b M c CO3, where 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.4, a+b+c=1, M is Fe 2+ , Cu 2+ and Zn 2+ One or more of the above, the sodium source includes sodium hydroxide or sodium carbonate, the mixing ratio of sodium salt and layered oxide precursor Na / Me is 0.95-1, and the chemical formula of the obtained sodium ion layered oxide positive electrode material substrate is Na x Ni a Mn b M c O2, wherein 0.9≤x≤1.0. The sintering conditions are as follows: a temperature of 850-980°C, with typical but non-limiting sintering temperatures of 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, and a sintering time of 8-15 hours, with typical but non-limiting reaction times of 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, and 15 hours.

[0033] Step S12, mixing tungstic acid and sodium salt and reacting them to obtain a slurry-like sodium tungstate coating material.

[0034] When tungstic acid and sodium salt are mixed, the molar ratio of tungsten to sodium is 1:2, and the two react when mixed to directly obtain a slurry-like sodium tungstate coating material. The sodium salt is sodium carbonate or sodium hydroxide, or a mixture of sodium carbonate and sodium hydroxide.

[0035] Step S13, respectively adding the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate into the organic solvent according to a preset ratio, stirring and mixing, filtering and drying, and performing heat treatment to obtain a coated sodium ion layered oxide positive electrode material.

[0036] The preset ratio of the sodium tungstate coating material to the sodium ion layered oxide cathode material substrate is a molar ratio of 0.1 to 5:100, and the typical but non-limiting molar ratio is 0.1:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100. The organic solvent is ethanol, isopropanol or ethylene glycol.

[0037] After adding the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate into the organic solvent, the stirring and mixing time is 15 to 120 minutes. The typical but non-limiting mixing and stirring time is 15 minutes, 30 minutes, 45 minutes, 60 minutes, 75 minutes, 90 minutes, 105 minutes, and 120 minutes.

[0038] The organic solvent is filtered and dried, and then heat treated. The heat treatment conditions are: temperature between 400 and 750°C, and typical but non-limiting heat treatment temperatures are 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, and 750°C; time is between 8 and 15 hours, and typical but non-limiting heat treatment times are 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, and 15 hours.

[0039] If necessary according to actual needs, further crushing operation can be carried out.

[0040] The present invention uses tungstic acid and sodium salt to directly react to generate a slurry-like sodium tungstate coating material, and then performs liquid phase coating on the positive electrode material substrate, and utilizes the good conductivity of sodium tungstate to provide a fast transmission channel for sodium ion diffusion, which is beneficial to improve the ion transmission rate in the positive electrode material during charging and discharging, reduce the impedance of sodium ion diffusion, and improve the rate performance of the material. At the same time, the coating layer protects the surface of the positive electrode material, improves the stability of the interface, can effectively reduce the side reactions on the surface of the positive electrode material, and is beneficial to improve the cycle stability of the positive electrode material. Secondly, the coating layer formed by liquid phase coating in the present invention has a controllable thickness, and the particles are not easy to agglomerate, which can effectively improve the uniformity of the coating.

[0041] According to the second aspect of the present invention, the present invention also provides a coated sodium ion layered oxide positive electrode material prepared according to the above preparation method, which has the same technical effects as the above embodiment and will not be described in detail here.

[0042] In addition, the present invention also provides a sodium ion battery, including a coated sodium ion layered oxide positive electrode material prepared according to the above-mentioned preparation method, and also including a negative electrode material, a separator, an electrolyte, etc. that can be obtained from the scheme disclosed in the prior art. The sodium ion battery also has the same beneficial effects as the above-mentioned embodiment, which will not be repeated here.

[0043] The present invention is further described below by way of examples and comparative examples. Unless otherwise specified, the materials in the examples and comparative examples are prepared according to existing methods or purchased directly from the market.

[0044] Embodiment 1:

[0045] The layered oxide precursor Ni 0.32 Fe 0.34 Mn 0.34 (OH)2 and sodium carbonate are mixed, wherein Na / Me=1, mixed by a high-speed mixer, sintered at 955°C for 12 hours and crushed to obtain a sodium ion layered oxide positive electrode material substrate. At the same time, tungstic acid and sodium hydroxide are mixed, wherein the molar ratio of tungsten to sodium is 1:2, and a slurry of sodium tungstate coating material is obtained after sufficient reaction. Then, the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate are added to ethanol respectively, stirred and mixed for 15 minutes, filtered and dried, and heat treated at 450°C for 12 hours to obtain a coated sodium ion layered oxide positive electrode material, wherein the molar ratio of sodium tungstate to the sodium ion layered oxide positive electrode material substrate is 0.1%.

[0046] The prepared coated sodium ion layered oxide positive electrode material was measured for XRD pattern, such as Figure 2 As shown, it can be seen that sodium tungstate and O3 type sodium ion layered oxide are generated. Embodiment 2:

[0047] The layered oxide precursor Ni 0.32 Fe 0.34 Mn 0.34(OH)2 and sodium carbonate are mixed, wherein Na / Me=1, mixed by a high-speed mixer, sintered at 955°C for 12 hours and crushed to obtain a sodium ion layered oxide positive electrode material substrate. At the same time, tungstic acid and sodium hydroxide are mixed, wherein the molar ratio of tungsten to sodium is 1:2, and a slurry of sodium tungstate coating material is obtained after sufficient reaction. Then, the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate are added to ethanol respectively, stirred and mixed for 15 minutes, filtered and dried, and heat treated at 550°C for 12 hours to obtain a coated sodium ion layered oxide positive electrode material, wherein the molar ratio of sodium tungstate to the sodium ion layered oxide positive electrode material substrate is 0.2%.

[0048] Embodiment 3:

[0049] The layered oxide precursor Ni 0.32 Fe 0.34 Mn 0.34 (OH)2 and sodium carbonate are mixed, wherein Na / Me=1, mixed by a high-speed mixer, sintered at 955°C for 12 hours and crushed to obtain a sodium ion layered oxide positive electrode material substrate. At the same time, tungstic acid and sodium hydroxide are mixed, wherein the molar ratio of tungsten to sodium is 1:2, and a slurry of sodium tungstate coating material is obtained after sufficient reaction. Then, the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate are added to ethanol respectively, stirred and mixed for 15 minutes, filtered and dried, and heat treated at 600°C for 12 hours to obtain a coated sodium ion layered oxide positive electrode material, wherein the molar ratio of sodium tungstate to the sodium ion layered oxide positive electrode material substrate is 0.2%.

[0050] Comparative Example:

[0051] The layered oxide precursor Ni 0.32 Fe 0.34 Mn 0.34 (OH)2 and sodium carbonate are mixed, wherein Na / Me=1, and after mixing in a high-speed mixer, they are sintered at 955°C for 12 hours and crushed to obtain a sodium ion layered oxide positive electrode material substrate.

[0052] After button-type batteries were made of the coated sodium ion layered oxide positive electrode materials (Examples 1-3) prepared by the present invention and the sodium ion layered oxide positive electrode material substrates not coated with sodium tungstate (Comparative Example), the final rate performance and cycle performance tests were respectively carried out. The test results are as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the rate performance of the coated sodium ion layered oxide positive electrode material prepared by the present invention is 20%-30% higher than that of the sodium ion layered oxide positive electrode material substrate not coated with sodium tungstate, which obviously shows better rate performance. Figure 4 It can be seen that the coated sodium ion layered oxide positive electrode material prepared by the present invention also shows better cycle performance, especially after 100 cycles, it shows significantly better cycle performance, which is nearly 10% higher than the cycle performance of the sodium ion layered oxide positive electrode material not coated with sodium tungstate.

[0053] The specific embodiments described in the present invention are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the attached claims.

[0054] Although the present invention has been described in detail and some specific embodiments have been cited, it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention.

Claims

1. A method for preparing a coated sodium ion layered oxide positive electrode material, characterized in that: Includes steps: S11: preparing a powdered sodium ion layered oxide positive electrode material substrate using a layered oxide precursor and a sodium salt; S12: mixing tungstic acid and sodium salt and reacting them to obtain a slurry-like sodium tungstate coating material; when the tungstic acid and the sodium salt are mixed, the molar ratio of tungsten to sodium is 1:2; S13: respectively adding the sodium tungstate coating material and the sodium ion layered oxide positive electrode material substrate into an organic solvent according to a preset ratio, performing liquid phase coating on the sodium ion layered oxide positive electrode material substrate, stirring and mixing, filtering and drying, and performing heat treatment to obtain a coated sodium ion layered oxide positive electrode material, wherein the preset ratio is a molar ratio of 0.1 to 5:100, and the stirring and mixing time is 15 to 120 minutes; the heat treatment conditions are: temperature at 400 to 750°C, and time at 8 to 15 hours.

2. The preparation method according to claim 1, characterized in that: The sodium salt is sodium carbonate and / or sodium hydroxide.

3. The preparation method according to claim 2, characterized in that: The organic solvent is ethanol, isopropanol or ethylene glycol.

4. The preparation method according to claim 1, characterized in that: The step of preparing a powdered sodium ion layered oxide positive electrode material substrate using a layered oxide precursor and a sodium salt comprises: The layered oxide precursor and the sodium salt are mixed uniformly, wherein the chemical formula of the layered oxide precursor is Ni a Mn b M c (OH)2 or Ni a Mn b M c CO3, where 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.4, a+b+c=1, M is Fe 2+ , Cu 2+ and Zn 2+ One or more of; The mixed materials are sintered and crushed to obtain the sodium ion layered oxide positive electrode material substrate having a chemical formula of Na x Ni a Mn b M c O2, where 0.9≤x≤1.

0.

5. The preparation method according to claim 4, characterized in that: The sintering conditions are: temperature between 850°C and 980°C, and time between 8 and 15 hours.

6. A coated sodium ion layered oxide positive electrode material obtained by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method and application of coated layered sodium ion positive electrode material

    CN115377392A